OpenFOAM-preCICE: Coupling OpenFOAM with External Solvers for Multi-Physics Simulations - Chourdakis, Gerasimos; Schneider, David; Uekermann, Benjamin (OpenFOAM® Journal, 2023)
Multi-physics simulations, such as conjugate heat transfer or fluid-structure interaction, are often constructed completely in OpenFOAM. However, they can also be formed by coupling OpenFOAM to third-party simulation software via a coupling tool. This approach indirectly adds to the capabilities of OpenFOAM those of other simulation tools (such as physical models or discretization methods more fitting for specific applications), and allows building complex multi-physics simulations by connecting specialized single-physics codes. We present the OpenFOAM-preCICE adapter, a function object that enables standard OpenFOAM solvers to use the open-source, massively parallel coupling library preCICE, without requiring any code modifications. We review alternative coupling approaches, analyze our design decisions, peek into key implementation details, validate the adapter, study the effect on runtime, and give an overview of the growing community of users and contributors.